Efektivitas Bimbingan Konseling Kristen Oleh Guru PAK Pada Peningkatan Motivasi Belajar Siswa Kelas XII Berlatar Belakang Broken Home Di SMK Swasta HKBP Sidikalang Tahun Ajaran 2023/2024 - Arnita Flora Simarmata; Betty A.S Pakpahan; Maria Widiastuti; Lince Sihombing; Iwan Setiawan Tarigan (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
This research aims to determine the implementation and effectiveness of Christian Counseling Guidance provided by Effective Christian Religious Education and Character Teachers in Increasing the Learning Motivation of Class This research uses a semi-case study type of research and uses as informants eight students from broken home backgrounds and Christian Religious Education and Character Teachers. The results of this research show that the process of implementing Christian counseling guidance by PAK teachers starts from: service (attending), empathy, giving advice/encouragement, the final stage provides reinforcement and closes with prayer. Christian counseling guidance is considered effective in increasing the learning motivation of students from broken home backgrounds, this is assessed based on the results of the presentation of the students themselves and the Christian Religious Education and Character Education teachers. Changes in students' motivation began to appear after participating in Christian counseling activities, changes in students' motivation, who previously often daydreamed and did not pay attention to the learning process, are now starting to be enthusiastic about learning, starting to show interest in learning by studying more actively, doing homework/assignments, students who have feelings of worry and fear begins to disappear, they don't give up easily, they are happier and more confident in doing things (independently) and students have a commitment to achieving their goals and hopes in the future.